TRANSFORMASI DIGITAL DAN INDUSTRI HALAL PADA UMKM KABUPATEN BANYUWANGI - Azy Athoillah Yazid; Aunur Rofiq; Munawar Ismail (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
This article discusses how the postulates related to inheritance contained in the Qur'an and Sunnah (hadith) are then related to how the concepts contained in these arguments when entering investment products into the inheritance section or are said to be products the investment product is used as the object of inheritance itself. The output determines whether or not the products in the Investment can be used as objects of inheritance. As well as conducting a study of these arguments using a thematic method in which in the study the author determines which arguments will be used in accordance with the theme being carried and then examines them in detail starting from the origins, the sanad, and also about the validity of the arguments. Then also present other hadiths which, if related to the existing theme, are used as reinforcement from the previous hadith.